Pentingnya Pelajaran PKN di SD untuk Membentuk Karakter Peduli Lingkungan - Alya Hasna Sabita; Anestra Putri Fauziah; Adrias Adrias (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This article aims to determine how important Civic Education learning is in schools, one of which is in elementary schools, to form a character that cares about the environment. This study uses the SLR (Systematic Literature Review) method where researchers search for and review various sources such as journals, books, or other sources that are in accordance with the topic to be discussed. Civic Education learning in elementary schools is a very important learning in forming a character that cares about the school environment. By integrating Civic Education learning in elementary schools, it can develop awareness to be able to form a character that cares about the environment. The results of this study are that Civic Education learning has a very important influence on the formation of a character that cares about the environment